2009
DOI: 10.1016/j.bpj.2009.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of the Lateral Structure of Porcine Brain Cerebrosides/POPC Mixtures in Presence and Absence of Cholesterol

Abstract: We studied the thermal behavior of membranes composed of mixtures of natural cerebrosides (from porcine brain) and 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) with and without cholesterol, using differential scanning calorimetry, Fourier transform infrared spectroscopy, and confocal/multiphoton fluorescence microscopy. The POPC/cerebroside mixture display solid ordered/liquid disordered phase coexistence in a broad range of compositions and temperatures in agreement with previous results reported f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…In contrast, cholesterol transbilayer distribution remains unclear; several studies, however, reached the same conclusion that a significant part (50-75 %) is distributed in the inner leaflet [5,6]. Membrane cholesterol plays key regulatory roles including (1) membrane fluidity via lipid ordering; (2) membrane deformability by modulation of plasma membrane protein interactions at the interface with cortical cytoskeleton [7]; (3) formation and stabilization of nanometric lipid assemblies, rafts and caveolae [2,4], as important signaling platforms [8][9][10]; and (4) phase coexistence in artificial membranes [11][12][13]. Cholesterol is, thus, a key component of membrane biology and the concept of its clustering into membrane domains is attractive to explain its different functions.…”
Section: Introductionmentioning
confidence: 70%
“…In contrast, cholesterol transbilayer distribution remains unclear; several studies, however, reached the same conclusion that a significant part (50-75 %) is distributed in the inner leaflet [5,6]. Membrane cholesterol plays key regulatory roles including (1) membrane fluidity via lipid ordering; (2) membrane deformability by modulation of plasma membrane protein interactions at the interface with cortical cytoskeleton [7]; (3) formation and stabilization of nanometric lipid assemblies, rafts and caveolae [2,4], as important signaling platforms [8][9][10]; and (4) phase coexistence in artificial membranes [11][12][13]. Cholesterol is, thus, a key component of membrane biology and the concept of its clustering into membrane domains is attractive to explain its different functions.…”
Section: Introductionmentioning
confidence: 70%
“…This behavior is similar to that observed with SM, although the transition to the l o phase is well established even before reaching the 8 mol % Chol. In the case of Cer, the s o domains remain solid-like still with concentrations of Chol higher than 20 mol % [97], as previously commented.…”
Section: Sphingolipids and Chol In Model Slbsmentioning
confidence: 79%
“…Combination of alternative fl uorophore labeling is not without potential pitfalls. The impact of sphingolipid headgroups on lateral lipid organization has been demonstrated in artifi cial membranes ( 51 ). Moreover, we recently reported that BODIPY-GlcCer/GM1BODIPY and BODIPY-SM, built on the very same BODIPY-ceramide backbone and differing only by their respective polar head, segregated into distinct domains exhibiting different properties ( 20 ).…”
Section: Bodipy-lipid Domains Show Preferential Protein Association Amentioning
confidence: 95%